The promotional role of Nd on the catalytic activity and hydrothermal stability of Cu-SAPO-18 catalyst for NH3-SCR reaction. (19th May 2022) - Qin, Kaiwei; Ming, Shujun; Chen, Zhen; Zhang, Shoute; Meng, Ying; Wu, Qin; Bian, Ce; Liu, Qian; Guo, Lei; Li, Dan; Pang, Lei; Li, Tao
Abstract : The Cu-SAPO-18 was prepared by the one-pot method and modified through hydrothermal post-treatment, metal-doped Nd(x)/Cu-SAPO-18 (x = 0.4, 0.8, 1.2, 1.6) catalysts were obtained. The catalytic performance of fresh and aged Nd(x)/Cu-SAPO-18 was evaluated by ammonia selective catalytic reduction (NH3 -SCR) reaction. The NOx conversion rate of Nd (1.2)/Cu-SAPO-18 was highest. More than 94.5% NOx conversion was maintained over the aged Nd(x)/Cu-SAPO-18 during 250–450°C, which was almost 10% higher than the conversion of aged Cu-SAPO-18. Various techniques including XRD, XRF, BET, SEM, 27 Al MAS NMR, XPS, UV-vis, NH3 -TPD, H2 -TPR, were applied to explore the effect of Nd content on the physiochemistry property of Cu-SAPO-18. The addition of Nd effectively maintained the relatively large specific surface area and uniform pore size distribution. Moreover, the dealumination progress of Cu-SAPO-18 was mitigated and the aggregation of copper species during hydrothermal aging process was restrained. Thus, Nd(x)/Cu-SAPO-18 owed less CuOx and more amount of isolated Cu 2+ ions, which stabilized catalyst structure by entering the double 6-membered ring (D6R). Meanwhile, the incorporation of Nd enhanced the redox property and stabilised surface acid sites of Cu-SAPO-18, which were responsible for facilitating the adsorption and activation of reactants. GRAPHICAL ABSTRACT: UF0001